The Influence of Perceived Value, Brand Awareness, Health Consciousness, and Product Variety towards Repurchase Intention through Purchase Intention and Purchase Decision - Hudyah Astuti Sudirman; Marsha Anindita; Aisyiyah Muntiara Putri (IECON: International Economics and Business Conference, 2025)
This study aims to analyze and prove perceived brand awareness and health consciousness and product variety on repurchase intention through purchase intention and purchase decision on Ultra Milk consumers in Samarinda. This study used a questionnaire with a sample of 145 Ultra Milk consumers in Samarinda. This research uses a quantitative approach with path analysis which is processed with IBM SPSS Statistics 23 software and Structural Equation Modeling (SEM) with AMOS 23 software. this research uses a method or approach that has been determined by distributing a sample questionnaire of 145 Ultra Milk consumers in Samarinda, sampling using the accidental random sampling technique. By conducting instruments, namely validity and reliability tests and classical assumption tests such as normality tests and multicollinearity tests, then estimation tests and structural model fit tests are carried out. Based on the structural model, it can be concluded that there is a significant relationship between the variables perceived value, brand awareness, health consciousness and product variety to purchase intention; purchase value, product variety, purchase intention to purchase decision; purchase decisions and products variety to repurchase intention.